Advances in Experimental Medicine and Biology
DOI: 10.1007/0-306-46832-8_6
|View full text |Cite
|
Sign up to set email alerts
|

Somatostatin and Opioid Receptors in Mammary Tissue

Abstract: Somatostatin and opioid systems, are the two main inhibitory systems in mammals. Both classes of substances have been identified in normal and malignant mammary gland, as well as their cognitive receptors. They have been implied in the inhibition of cell growth of cancer cells and cell lines, in a dose-dependent and reversible manner. Somatostatin acts through homologous receptors (SSTRs), belonging to five distinct classes (SSTR1-5). We, and others have identified SSTR2 and 3 as been the only SSTRs present in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0
1

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 36 publications
1
12
0
1
Order By: Relevance
“…namely, opioid receptor κ1 (OPRK1), somatostatin receptor 1 (SSTR1), endothelin receptor A (EDNRA), and endothelin receptor B (EDNRB), are known for their inhibitory effects on cell growth. (8)(9)(10)(11) This is in theoretical accordance with the downregulation of these genes observed between NC and CA (Fig. 4b, Table 3), as this would give cells a growth advantage.…”
Section: Discussionsupporting
confidence: 87%
“…namely, opioid receptor κ1 (OPRK1), somatostatin receptor 1 (SSTR1), endothelin receptor A (EDNRA), and endothelin receptor B (EDNRB), are known for their inhibitory effects on cell growth. (8)(9)(10)(11) This is in theoretical accordance with the downregulation of these genes observed between NC and CA (Fig. 4b, Table 3), as this would give cells a growth advantage.…”
Section: Discussionsupporting
confidence: 87%
“…The expression of cortactin is increased in some breast carcinomas, and overexpression of the gene modifies the invasive properties of the mammary cells (Kairouz and Daly, 2000). Cortactin also interacts with somatostatin receptor subtype 2 (SSTR2) through cortactin-binding protein 1 (Zitzer et al ., 1999), while SSTR2 mediates growth inhibitory signal of somatostatin in the mammary cells (Hatzoglou et al ., 2000). Though it is unknown which cortactin isoform is major in other tissues, the isoform C, which was the major isoform in the mammary gland, is reported to bind to CBP90 (Ohoka and Takai, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…16,17 Somatostatin and opioid systems are the two main inhibitory systems in mammals. 18 SMS acts through homologue receptors (SSTRs), belonging to five distinct classes (SSTR 1-5). 18 Octreotide, one of the most used SMS analogues, which acts preferentially via somatostatin receptor subtype 2 (SSTR-2), is an inhibitor of tyrosine kinase (TK).…”
Section: Introductionmentioning
confidence: 99%
“…18 SMS acts through homologue receptors (SSTRs), belonging to five distinct classes (SSTR 1-5). 18 Octreotide, one of the most used SMS analogues, which acts preferentially via somatostatin receptor subtype 2 (SSTR-2), is an inhibitor of tyrosine kinase (TK). Several trials showed that SMS or its analogues could reduce the proliferative activity of tumor cells.…”
Section: Introductionmentioning
confidence: 99%